Addomesticare la comunicazione accademica e quella istituzionale attraverso un video per il web - Mezzadri, Marco (Educazione Linguistica Language Education, 2012)
The aim of this article is to present the process of creation of a video, conceived mainly for online use, which has been designed to inform on a teaching and research project developed in 2010-2011 by Parma University, Provincia di Parma local authority, Cariparma Foundation, a network of highschools, and local school authorities.